Implementing Enterprise 2.0 Knowledge Sharing Tools In An Eastern European Consultancy - Bocaneanu, Sara (Journal of Knowledge Management Practice, 2009)
Enterprise 2.0 technologies are being introduced to support cutting-edge knowledge management in many companies. They are however, poorly known in Eastern European countries. This article presents a case study of the implementation of three major Enterprise 2.0 tools in a Eastern European consultancy firm. The tools include social bookmarking, wikis and social authoring, and the article examines how the software was introduced, benefits sought, actual usage and difficulties encountered. Conclusions are offered as recommendations for further implementation.